Penerapan Konseling Individual dengan Teknik Rasional Emotif Behavior untuk Mengatasi School Refusal Pada Santriwati (Studi Kasus Klien “R” di Pondok Pesantren Sabilul Muhtadin) - Eka Fitria; Abdur Razzaq; Emi Puspita Dewi (Scidac Plus, 2024)
School refusal is school refusal behavior that is motivated by unwillingness to attend school or finding it difficult to stay at school all day. This research aims to determine the description of school refusal in client